A snapshot of challenges and opportunities faced by the scientific workforce in liver transplantation: a survey of the International Liver Transplantation Society (ILTS) - Czigány, Zoltán; Putri, Aghnia Jolanda; Jiang, Decan; Meier, Raphael; Emamaullee, Juliet; Al-Adra, David P.; Pang, Li; Kim, Joohyun; Krendl, Felix J.; Verstegen, Monique M. A.; Meister, Franziska A.; Lurje, Georg; et al. (Liver transplantation, 2025)
Basic and translational research (B&TR) in liver transplantation (LT) underwent considerable changes and shifts over the past decade. To capture the current landscape and future potential of B&TR in LT, we conducted an online survey within the International Liver Transplantation Society (ILTS) community. The survey aimed to collect comprehensive data on the respondents' characteristics, qualifications, experiences, and research activities, providing the present state and future directions of B&TR in LT. Between October 2023 and January 2024, an online survey consisting of 35 key items was distributed to the ILTS community through newsletters and social media channels. Data were analyzed using a combination of quantitative and qualitative methods. The survey gathered 153 valid responses, with 79% of respondents possessing relevant experience in B&TR and 76% reporting concurrent clinical duties. Some 62% hold faculty positions, with 34% identifying as MDs and 44% holding combined MD/PhD degrees. About 71% of scientists with clinical duties reported challenges in conducting B&TR, with 57% citing a lack of time and 41% pointing to insufficient funding. Nevertheless, 69% of respondents currently receive research funding, with 58% supported by government or public sources. Among early career researchers, 57% reported receiving average or poor mentoring, and 30% indicated insufficient protected time for research. Looking ahead, advancing technologies, machine learning/artificial intelligence, multi-omics, xenotransplantation, and machine perfusion were highlighted as areas with the potential to significantly shift the paradigm in the near future. Our survey captured insights from B&TR scientists within the ILTS, identifying both challenges and opportunities for future developments and aiding in the strategic direction of the society’s initiatives. - - - - - Export